A survey of recent studieson chlorophyll variation in Indian coastal waters. Issue 1 (December 2020) - Tholkapiyan, M.; Mohan, A.; Vijayan., D. S
Abstract: Understanding the pattern of chlorophyll in the open and coastal waters were greatly helpful for the primary productivity and the underwater light field distribution. Sensors were used for the measurements were plays a major role to quantify the amount of chlorophyll. Several studies were conducted for the analysis of chlorophyll pattern over the Indian coastal water. In this study, we conducted a literal survey on the recent studies on the chlorophyll variations. For that, first we presented the chlorophyll measurement techniques, then existing algorithms for the retrieval of chlorophyll, finally we analyzed the various studies conductedfor the chlorophyll distribution and their effects. The integrated use of this survey greatly used to develop new techniques for the coastal zone management and forecasting the environmental changes.